2011
DOI: 10.1007/s00221-011-2541-2
|View full text |Cite
|
Sign up to set email alerts
|

Motor equivalence and self-motion induced by different movement speeds

Abstract: This study investigated pointing movements in 3D asking two questions: (1) Is goal-directed reaching accompanied by self-motion, a component of the joint velocity vector that leaves the hand’s movement unaffected? (2) Are differences in the terminal joint configurations among different speeds of reaching motor equivalent (i.e., terminal joint configurations differ more in directions of joint space that do not produce different pointer-tip positions than in directions that do) or non-motor equivalent (i.e., ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 41 publications
1
20
0
Order By: Relevance
“…Another method of analysis of synergies based on individual trials has been suggested recently based on measurement of deviations of a multi-element system along the UCM and ORT spaces (Scholz et al 2011; Mattos et al 2011, 2015). This method compares motor equivalent (ME, within the UCM) and non-motor equivalent (nME, within ORT) deviations of the system during quick actions.…”
Section: Discussionmentioning
confidence: 99%
“…Another method of analysis of synergies based on individual trials has been suggested recently based on measurement of deviations of a multi-element system along the UCM and ORT spaces (Scholz et al 2011; Mattos et al 2011, 2015). This method compares motor equivalent (ME, within the UCM) and non-motor equivalent (nME, within ORT) deviations of the system during quick actions.…”
Section: Discussionmentioning
confidence: 99%
“…Another consideration is the difference in the movement speed with different events. It has been shown that as movement speed increases so does V UCM but not V Orth (Scholz, Dwight-Higgin, Lynch, Tseng, Martin, Schöner, 2011). Although the values of V UCM and V Orth are calculated separately for each event for each player, the player's values may align differently when the mean group value for the different normalisation methods.…”
Section: Time Normalization Vs Swing Anglesmentioning
confidence: 99%
“…If a system produces a desired value or time profile of a salient performance variable, large deviations in directions that keep this variable unchanged (motor equivalent, ME) are expected. Large ME deviations have been observed in several earlier studies (Scholz et al 2007;Mattos et al 2011;Scholz et al 2011;Mattos et al 2013;Mattos et al 2015).…”
Section: Task-specific Stability In Abundant Systemsmentioning
confidence: 53%
“…Assuming somewhat different initial conditions and force fields across trials, one expects relatively high inter-trial variance in less stable directions and low inter-trial variance in more stable directions. Relatively recently a complementary method has been introduced based on observation of system's trajectories during quick actions (Mattos et al 2011;Scholz et al 2011). This method assumes that a neural input into the system associated with a quick action may be viewed as a perturbation expected to cause relatively large deviations of the system in directions of low-stability.…”
Section: Task-specific Stability In Abundant Systemsmentioning
confidence: 99%